IBN Sino’s Thoughts on the Importance of Physical Exercises in Living a Healthy Lifestyle - Shermatov G’. Қ. (European Journal of Life Safety and Stability (2660-9630), 2021)
A healthy lifestyle is defined as the care and attention of a person to his or her body in order to maintain the health given to him or her by nature. In his five-year book, The Laws of Medicine, the Sultan of Medicine outlines a series of factors that affect health.